Double writing: Ralph Waldo Emerson's theoretical poetics - Pickford, Benjamin (2014)
This thesis considers Ralph Waldo Emerson’s compositional process of ‘double writing’ as a distinctly theorised and intellectually coherent practice that generated discrete bodies of text: his private journals and notebooks; and the public essays, lectures, and poems. Throughout Emerson scholarship, critics tend to quote the two bodies without differentiation, often either neglecting the issue of their coexistence or asserting the priority of one form over the other. I contend instead that principles of self-reading, accretive reinscription, and a perpetuated relation to his own text condition Emerson’s ideas of poetic agency and the role of literature in broader socio-cultural contexts, to the extent that they become the preeminent factor in shaping his philosophical and literary aspirations. Focusing on the period 1836-50, from the beginning of the coexistence of public and private corpuses to the point at which he finalises his theory of textual relation, I trace the way in which Emerson’s ongoing textual investment first echoes—and later disrupts—aspirations to realise a philosophy of the subject steeped in the romantic tradition. The first part of the thesis examines the two textual bodies insofar as they reflect upon each other and on theories of composition, finding that Emerson gradually loses faith in the function of his public works up to 1842. In the second section of the thesis, I illustrate the continual revision his relation to text undergoes in the major works of the 1840s, as his compositional theory adapts to first conceptualise and then fulfil certain ethical obligations of the scholar and poet. I end by examining the poetic apotheosis figured by Poems (1847) and Representative Men (1850), which has little in common with his youthful aspirations, but which explains the ‘sage’-like mantle he accepted in American life and letters from the 1850s until his death in 1882. As well as revising conceptions of Emerson’s literary agency and the structure of his canon, this thesis offers an original reading of the theory of an author’s socio-cultural role in the mid nineteenth-century through the example of one of the era’s major figures.